A strontium bismuth titanate-based dielectric energy storage ceramic material with high energy storage density and low loss, wide temperature and frequency stability and a preparation method thereof
Patent Information
- Application Number
- CN202611506135.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-26
- Publication Date
- 2026-10-30
AI Technical Summary
现有改性工作虽然能够实现极性纳米微区的调控,但其可恢复储能密度依旧处于有限水平,难以适配脉冲功率器件小型化发展对高储能密度介质的现实要求
[0020]1.在烧结温度上,比同类型的钛酸锶铋基介电陶瓷的烧结温度低,其烧结温度为(1200~1250℃),且晶粒均匀,较好的提高了其烧结活性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dielectric electronic functional ceramic materials, specifically relating to a strontium bismuth titanate-based dielectric energy storage ceramic material with both high energy storage density and low loss, and wide temperature and frequency stability, and its preparation method. Background Technology
[0002] With the continuous development of pulse power, military, and power electronic equipment, there is a growing demand for miniaturization and lightweighting of energy storage capacitors. Dielectric ceramic capacitors, with their outstanding advantages such as fast charging and discharging speeds, high power density, high voltage resistance, and long cycle life, are crucial fundamental components in high-energy pulse power systems. The total energy density (W) of dielectric capacitors is calculated based on integral calculations. total ), energy loss (W) loss ), efficiency (η) and recoverable energy density (W) rec Dielectric energy storage materials are insulating materials that store electrical energy through dielectric polarization, primarily used in high-power pulse power supplies, power electronics, and other fields. However, current ceramic dielectric energy storage materials generally suffer from low energy density, resulting in energy storage devices using them as the core medium being typically large and heavy. This deficiency not only significantly restricts the widespread use of these materials in high-performance energy storage scenarios but also hinders the iterative development of pulse power systems and other equipment with ceramic capacitors as core components towards miniaturization, lightweighting, and multifunctional integration.
[0003]
[0004] Ding et al. introduced composite end-members Bi(Nb) into SBT ceramics. 1 / 3 Ni 2 / 3 O3 induces the formation of highly dynamic polar nanoregions, enabling the ceramic to achieve a high recoverable energy storage density of 3.71 J / cm³. 3 Kong et al. on 0.9(Sr 0.7 Bi 0.2 TiO3-0.1Bi(Mg) 0.5 Me 0.5 The energy storage performance of relaxor ferroelectric ceramics (Me=Ti, Zr, Hf) was studied, and the results were finally obtained at 0.9 (Sr 0.7 Bi 0.2 TiO3-0.1Bi(Mg) 0.5 Hf 0.5 The best energy storage performance was achieved in O3 ceramics, with a recoverable energy storage density of 3.1 J / cm³. 3The energy storage efficiency is 93%. Although existing modification work can achieve the control of polar nano-microregions, its recoverable energy storage density is still at a limited level, making it difficult to meet the practical requirements of high energy storage density media for the miniaturization of pulse power devices. For strontium bismuth titanate-based ceramics, it is still necessary to explore new composite modification end-members to further improve the recoverable energy storage density of the material. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a method for preparing a strontium bismuth titanate-based dielectric ceramic material that combines high energy density, low loss, and wide temperature and frequency stability. Furthermore, its energy density ranges from 3.1 to 5.37 J / cm³. 3 With an energy storage efficiency of 84.4%~86.78% and a loss tanδ of 0.00013~0.00023, it exhibits excellent stability over a wide temperature and frequency range, making it applicable to fields such as electronic power, military industry, and high-energy pulse power technology.
[0006] To achieve the above advantages, the present invention can be implemented through the following technical measures:
[0007] This invention provides a strontium bismuth titanate-based dielectric ceramic material with high energy density, low loss, and wide temperature and frequency stability, and its chemical formula is (1-x)Sr. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3, 0.05≤x≤0.20, where x is 0.05, 0.10, 0.15, or 0.20 respectively. This ceramic is processed with multi-ion Sr 2+ Bi 3+ Mg 2+ Ti 4+ 、Nb 5+ Co-doping enables multiple performance modulations by forming Bi vacancies at A sites through charge balance, localizing charge carriers, pinning oxygen vacancy migration, and reducing dielectric loss; Nb 5 ⁺ Occupying the B site generates orbital doping effects, and its 4d orbitals interact with the Ti matrix. 4 The 3D orbital hybrid coupling of ⁺ widens the bandgap and increases the breakdown field strength. The two work together to regulate polarization relaxation, suppress premature polarization saturation, and reduce residual polarization while maintaining a large polarization difference, thus achieving high energy storage density and efficiency.
[0008] The preparation method of strontium bismuth titanate-based dielectric energy storage ceramic material with high energy density, low loss, and wide temperature and frequency stability includes the following steps:
[0009] (1-x)Sr 0.7 Bi 0.2 TiO3-xBi2 / 3 (Mg 1 / 3 Nb 2 / 3 Preparation and secondary ball milling of O3 (0.05≤x≤0.20) ceramic powder
[0010] (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 (0.05≤x≤0.20) ceramics are made by adding carbonates or oxides, weighing, mixing and stirring the raw materials according to the general chemical formula, and mixing them in a mass ratio of raw materials: zirconium balls: dispersion medium of 1:6:1, and placing them in a polyurethane ball mill jar.
[0011] Furthermore, the ball mill jar is placed on a planetary ball mill and milled for 4-6 hours at a speed of 300-360 r / min, and then dried in a constant temperature drying oven at 80-100℃.
[0012] Furthermore, the dried powder was placed into a crucible, and the crucible was placed in a muffle furnace. The temperature was increased to 800-950℃ at 5℃ / min and held for 3-5 hours. After cooling to room temperature in the furnace, (1-x)Sr was obtained. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic powder was then milled twice and dried at a constant temperature of 80℃ to obtain (1-x)Sr. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3Nb 2 / 3 O3 powder material.
[0013] Granulation, tableting, and debinding
[0014] Furthermore, the powder dried after secondary milling is mixed with 5% PVA solution and granulated. The granulated powder is then passed through a 60-mesh 304 stainless steel sieve and pressed under 2-4 MPa into (1-x)Sr granules with a diameter of 8 mm and a thickness of 1-1.2 mm. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 initial billet.
[0015] Furthermore, the ceramic blank obtained above is heated to 600℃~650℃ at 2℃ / min and held for 3~4 hours, and then cooled in the furnace to obtain the ceramic body.
[0016] Sintering and silvering
[0017] Furthermore, the ceramic green body obtained after debinding is sintered at 1200~1250℃ and held at that temperature for 2~3 hours, with a heating rate of 10℃ / min for the first 1000℃ and 5℃ / min thereafter. After holding at that temperature, it is cooled in the furnace. The silvering process involves polishing the surface of the sintered and cooled sheet, ultrasonically cleaning it, brushing on high-temperature silver paste, and holding it at 600℃~700℃ for 10 minutes, with a heating rate of 5℃ / min.
[0018] Obtain (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic material, 0.05≤x≤0.20, where x is 0.05, 0.10, 0.15 or 0.20 respectively.
[0019] The beneficial effects of the technical solution of the present invention include:
[0020] 1. In terms of sintering temperature, it is lower than that of similar strontium bismuth titanate-based dielectric ceramics, with a sintering temperature of (1200~1250℃), and the grains are uniform, which improves its sintering activity.
[0021] 2. This strontium bismuth titanate-based energy storage ceramic has excellent energy storage density and efficiency, low loss, and can be used as a dielectric capacitor in fields such as electronic power, military industry, and high-energy pulse power technology. Attached Figure Description
[0022] To better illustrate the technical solution of the present invention in a more detailed manner, please refer to the following accompanying drawings and embodiments.
[0023] Figure 1 The image shows the XRD pattern of the ceramic in an embodiment of the present invention.
[0024] Figure 2 The images shown are electron microscope scans and average grain size diagrams from embodiments of the present invention.
[0025] Figure 3 The dielectric and loss diagrams for embodiments of the present invention are shown in the range of 1kHz to 1000kHz.
[0026] Figure 4 The dielectric temperature spectrum of the ceramic at 1 kHz and the dielectric spectrum of the ceramic at room temperature are shown in the embodiments of the present invention.
[0027] Figure 5 The diagram shows the hysteresis loop (PE) curve, energy storage density, and efficiency of an embodiment of the present invention. Detailed Implementation
[0028] The present invention will be described in detail below with reference to examples and embodiments, but this is not intended to limit the invention.
[0029] Example 1
[0030] 0.95Sr 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Preparation and secondary ball milling of O3 ceramic powder
[0031] Ingredients. Prepare the raw materials according to the general formula 0.95Sr. 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Weigh and mix the raw materials, zirconium balls, and dispersion medium in a mass ratio of 1:6:1, and place them in a polyurethane ball mill jar.
[0032] Furthermore, the ball mill jar is placed on a planetary ball mill and milled for 4-6 hours at a speed of 300-360 r / min, and then dried in a constant temperature drying oven at 80℃.
[0033] Further, the dried powder was placed into a crucible, and the crucible was placed in a muffle furnace. The temperature was increased to 800℃~950℃ at 5℃ / min and held for 3~5 hours. After the muffle furnace cooled to room temperature, strontium bismuth titanate-based ceramic powder was obtained. It was then milled a second time and dried at a constant temperature of 80℃ to obtain 0.95Sr 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder material.
[0034] Granulation, tableting, and debinding
[0035] Furthermore, the powder dried after secondary milling is mixed with 5% PVA solution and granulated. The granulated powder is then passed through a 60-mesh sieve and pressed into 0.95Sr sheets with a diameter of 8 mm and a thickness of 1.2-1.4 mm under a pressure of 2.5-4 MPa. 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic blank.
[0036] Furthermore, the ceramic blank obtained above is heated to 600℃~650℃ at 2℃ / min and held for 3~4 hours, and then cooled in the furnace to obtain the ceramic body.
[0037] sintering
[0038] Furthermore, the ceramic green body obtained from the debinding process was sintered at 1200~1250℃ and held at that temperature for 2 hours. The heating rate was 10℃ / min for the first 1000℃ and 5℃ / min for the subsequent temperature increases. After the holding period, the green body was cooled in the furnace to obtain the 0.95Sr. 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 dielectric ceramic material.
[0039] The 0.95Sr obtained by sintering 0.7 Bi 0.2 TiO3-0.05Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 The O3 ceramic material was ground using an agate mortar and pestle and then subjected to X-ray diffraction testing, such as... Figure 1 The XRD pattern shows that the main crystalline phase of the ceramic material in this embodiment is a pure perovskite structure, containing a second phase Bi. 1.74 Ti2O 6.624 . Figure 2 Image (a) is a scanning electron microscope image from this embodiment, showing that the ceramic samples are all densely sintered, without obvious pores and uniform grains. The sintered samples were processed into smooth sheets with a thickness of approximately 0.1~0.2 mm. After ultrasonication, a high-temperature silver electrode was prepared (heating at 5℃ / min to 600℃~700℃, holding for 10 min, and then cooling with the furnace). The dielectric properties and losses were then tested at -55~150℃ and at different frequencies. Figure 3 As shown in (a). Figure 4 The curve at x = 0.05 shows the relationship between the dielectric constant and temperature at 1 kHz in this embodiment. As x increases, the phase transition temperature (T...)... m As the temperature of the material moves to lower temperatures, the dielectric property ε gradually decreases, and the loss is 0.00016, as shown in Table 1. Figure 4 (b) shows the dielectric constant and dielectric loss curves of each component at room temperature as a function of frequency. It can be observed from the figure that as the frequency increases, the dielectric constant and dielectric loss of the ceramic sample of that component do not fluctuate significantly, exhibiting good frequency stability. Figure 5(a) The curve with x=0.05 shows the hysteresis loop of the ceramic material in this embodiment measured at room temperature. The test electric field is 410 kV / cm, and it can be seen that its maximum polarization intensity is 28.67 μC / cm. 2 ,like Figure 5 (b) As shown by x = 0.05, the energy storage density of the energy storage ceramic in this embodiment can reach 4.42 J / cm³ at room temperature. 3 The energy storage efficiency can reach 85.51%. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1.
[0040] Example 2
[0041] 0.9Sr 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Preparation and secondary ball milling of O3 ceramic powder
[0042] Ingredients. Prepare the raw materials according to the general formula 0.9Sr. 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Weigh and mix the raw materials, zirconium balls, and dispersion medium in a mass ratio of 1:6:1, and place them in a polyurethane ball mill jar.
[0043] Furthermore, the ball mill jar is placed on a planetary ball mill and milled for 4-6 hours at a speed of 300-360 r / min, and then dried in a constant temperature drying oven at 80℃.
[0044] Furthermore, the dried powder was placed into a crucible, and the crucible was placed in a muffle furnace. The temperature was increased to 800℃~950℃ at a rate of 5℃ / min, and held for 3~5 hours. After the muffle furnace cooled to room temperature, 0.9Sr was obtained. 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3Nb 2 / 3 O3 powder was then milled twice and dried at a constant temperature of 80°C to obtain 0.9Sr. 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder material.
[0045] Granulation, tableting, and debinding
[0046] Furthermore, the powder dried after secondary milling is mixed with a 5% PVA solution and granulated. The granulated powder is then passed through a 60-mesh sieve and pressed into 0.9Sr sheets with a diameter of 8 mm and a thickness of 1.2–1.4 mm under a pressure of 2.5–4 MPa. 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic blank.
[0047] Furthermore, the ceramic blank obtained above is heated to 600℃~650℃ at 2℃ / min and held for 3 hours, and then cooled in the furnace to obtain the ceramic body.
[0048] sintering
[0049] Furthermore, the ceramic green body obtained after debinding was sintered at 1200~1250℃ and held at that temperature for 2 hours. The heating rate was 10℃ / min for the first 1000℃, and then 5℃ / min for the subsequent temperature increases. After the holding period, the green body was cooled in the furnace to obtain the 0.9Sr. 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 dielectric ceramic material.
[0050] The 0.9Sr obtained by sintering 0.7 Bi 0.2 TiO3-0.1Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 The O3 ceramic material was ground using an agate mortar and pestle and then subjected to X-ray diffraction testing, such as... Figure 1 The XRD pattern shows that the main crystalline phase of the ceramic material in this embodiment is a pure perovskite structure, containing a second phase Bi. 1.74 Ti2O 6.624 . Figure 2 Image (b) is a scanning electron microscope image from this embodiment, showing that the ceramic sample is densely sintered with no obvious pores and uniform grains. The sintered sample was processed into a smooth sheet with a thickness of approximately 0.1~0.2 mm. After ultrasonication, a high-temperature silver electrode was prepared (heated to 600℃~700℃ at 5℃ / min, held for 10 min, and then cooled with the furnace). Its dielectric properties and losses were then tested at -55~150℃ and at different frequencies. Figure 3 As shown in (b). Figure 4 The curve at x = 0.10 shows the relationship between the dielectric constant and temperature at 1 kHz in this embodiment. As x increases, the phase transition temperature (T...)... mAs the position of the dielectric material moves to lower temperatures, its dielectric properties ε gradually decrease, and its loss is 0.00023, as shown in Table 1. Figure 4 (b) shows the dielectric constant and dielectric loss curves of each component at room temperature as a function of frequency. It can be observed from the figure that as the frequency increases, the dielectric constant and dielectric loss of the ceramic sample of that component do not fluctuate significantly, exhibiting good frequency stability. Figure 5 (a) The curve with x=0.10 shows the hysteresis loop of the ceramic material in this embodiment measured at room temperature. The test electric field is 380 kV / cm, and it can be seen that its maximum polarization intensity is 20.54 μC / cm. 2 ,like Figure 5 (b) As shown by x = 0.10, the energy storage density of the energy storage ceramic in this embodiment can reach 3.1 J / cm³ at room temperature. 3 The energy storage efficiency can reach 86.78%. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1.
[0051] Example 3
[0052] 0.85Sr 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Preparation and secondary ball milling of O3 ceramic powder
[0053] Ingredients. Prepare the raw materials according to the general formula 0.85Sr. 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Weigh and mix the raw materials, zirconium balls, and dispersion medium in a mass ratio of 1:6:1, and place them in a polyurethane ball mill jar.
[0054] Furthermore, the ball mill jar is placed on a planetary ball mill and milled for 4-6 hours at a speed of 300-360 r / min, and then dried in a constant temperature drying oven at 80℃.
[0055] Further, the dried powder was placed into a crucible, and the crucible was placed in a muffle furnace. The temperature was increased to 800℃~950℃ at 5℃ / min and held for 3~5 hours. After the muffle furnace cooled to room temperature, 0.85Sr was obtained. 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic powder was then milled twice and dried at a constant temperature of 80°C to obtain 0.85Sr. 0.7 Bi 0.2TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder material.
[0056] Granulation, tableting, and debinding
[0057] Furthermore, the powder dried after secondary milling is mixed with 5% PVA solution and granulated. The granulated powder is then passed through a 60-mesh sieve and pressed into 0.85Sr granules with a diameter of 8 mm and a thickness of 1.2-1.4 mm under a pressure of 2.5-4 MPa. 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic blank.
[0058] Furthermore, the ceramic blank obtained above is heated to 600℃~650℃ at 2℃ / min and held for 3 hours, and then cooled in the furnace to obtain the ceramic body.
[0059] sintering
[0060] Furthermore, the ceramic green body obtained after debinding was sintered at 1200~1250℃ and held for 2 hours, with the heating rate being 10℃ / min for the first 1000℃ and 5℃ / min for the subsequent temperature increase. After the holding period, it was cooled in the furnace to obtain the 0.85Sr. 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 dielectric ceramic material.
[0061] The 0.85Sr obtained by sintering 0.7 Bi 0.2 TiO3-0.15Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 The O3 ceramic material was ground using an agate mortar and pestle and then subjected to X-ray diffraction testing, such as... Figure 1 The XRD pattern shows that the main crystalline phase of the ceramic material in this embodiment is a pure perovskite structure, containing a second phase Bi. 1.74 Ti2O 6.624 . Figure 2Image (c) is a scanning electron microscope image from this embodiment, showing that the ceramic sample is densely sintered with no obvious pores and uniform grains. The sintered sample was processed into a smooth sheet with a thickness of approximately 0.1~0.2 mm. After ultrasonication, a high-temperature silver electrode was prepared (heated to 600℃~700℃ at 5℃ / min, held for 10 min, and then cooled with the furnace). Its dielectric properties and losses were then tested at -55~150℃ and at different frequencies. Figure 3 As shown in (c). Figure 4 The curve at x = 0.15 shows the relationship between the dielectric constant and temperature at 1 kHz in this embodiment. As x increases, the phase transition temperature (T...)... m As the temperature of the dielectric material moves to lower temperatures, the dielectric property ε gradually decreases, and the dielectric loss is 0.00017, as shown in Table 1. Figure 4 (b) shows the dielectric constant and dielectric loss curves of each component at room temperature as a function of frequency. It can be observed from the figure that as the frequency increases, the dielectric constant and dielectric loss of the ceramic sample of that component do not fluctuate significantly, exhibiting good frequency stability. Figure 5 (a) The curve with x=0.15 shows the hysteresis loop of the ceramic material in this embodiment measured at room temperature. The test electric field is 550 kV / cm, and it can be seen that its maximum polarization intensity is 24.18 μC / cm. 2 ,like Figure 5 (b) As shown by x = 0.15, the energy storage density of the energy storage ceramic in this embodiment can reach 5.32 J / cm³ at room temperature. 3 The energy storage efficiency can reach 85.68%. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1.
[0062] Example 4
[0063] 0.8Sr 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Preparation and secondary ball milling of O3 ceramic powder
[0064] Ingredients. Prepare the raw materials according to the general formula 0.8Sr 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 Weigh and mix the raw materials, zirconium balls, and dispersion medium in a mass ratio of 1:6:1, and place them in a polyurethane ball mill jar.
[0065] Furthermore, the ball mill jar is placed on a planetary ball mill and milled for 4-6 hours at a speed of 300-360 r / min, and then dried in a constant temperature drying oven at 80℃.
[0066] Further, the dried powder was placed into a crucible, and the crucible was placed in a muffle furnace. The temperature was increased to 800℃~950℃ at 5℃ / min and held for 3~5 hours. After the muffle furnace cooled to room temperature, 0.8Sr was obtained. 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3Nb 2 / 3 O3 powder was then milled twice and dried at a constant temperature of 80°C to obtain 0.8Sr. 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder material.
[0067] Granulation, tableting, and debinding
[0068] Furthermore, the powder dried after secondary milling is mixed with 5% PVA solution and granulated. The granulated powder is then passed through a 60-mesh sieve and pressed into 0.8Sr sheets with a diameter of 8 mm and a thickness of 1.2-1.4 mm under a pressure of 2.5-4 MPa. 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 ceramic blank.
[0069] Furthermore, the ceramic blank obtained above is heated to 600℃~650℃ at 2℃ / min and held for 3 hours, and then cooled in the furnace to obtain the ceramic body.
[0070] sintering
[0071] Furthermore, the ceramic green body obtained from the debinding process was sintered at 1200~1250℃ and held at that temperature for 2 hours. The heating rate was 10℃ / min for the first 1000℃ and 5℃ / min for the subsequent temperature increases. After the holding period, the green body was cooled in the furnace to obtain the 0.8Sr. 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 dielectric ceramic material.
[0072] The 0.8Sr obtained by sintering 0.7 Bi 0.2 TiO3-0.2Bi 2 / 3 (Mg 1 / 3 Nb 2 / 3 The O3 ceramic material was ground using an agate mortar and pestle and then subjected to X-ray diffraction testing, such as... Figure 1 The XRD pattern shows that the main crystalline phase of the ceramic material in this embodiment is a pure perovskite structure, containing a second phase Bi. 1.74 Ti2O 6.624 . Figure 2 Image (d) is a scanning electron microscope image from this embodiment, showing that the ceramic sample is densely sintered with no obvious pores and uniform grains. The sintered sample was processed into a thin sheet with smooth surfaces and a thickness of approximately 0.1~0.2 mm. After ultrasonication, a high-temperature silver electrode was prepared (heated to 600℃~700℃ at 5℃ / min, held for 10 min, and then cooled with the furnace). Its dielectric properties and losses were then tested at -55~150℃ and at different frequencies. Figure 3 As shown in (d). Figure 4 The curve at x = 0.20 shows the relationship between the dielectric constant and temperature at 1 kHz in this embodiment. As x increases, the phase transition temperature (T...)... m As the position of the dielectric material moves to lower temperatures, its dielectric properties ε gradually decrease, and its loss is 0.00013, as shown in Table 1. Figure 4 (b) shows the dielectric constant and dielectric loss curves of each component at room temperature as a function of frequency. It can be observed from the figure that as the frequency increases, the dielectric constant and dielectric loss of the ceramic sample of that component do not fluctuate significantly, exhibiting good frequency stability. Figure 5 (a) The curve with x=0.20 shows the hysteresis loop of the ceramic material in this embodiment measured at room temperature. The test electric field is 570 kV / cm, and it can be seen that its maximum polarization intensity is 22.96 μC / cm. 2 ,like Figure 5 (b) As shown by x = 0.20, the energy storage density of the energy storage ceramic in this embodiment can reach 5.37 J / cm³ at room temperature. 3 The energy storage efficiency can reach 84.4%. The energy storage characteristics of the energy storage ceramic material in this embodiment at room temperature are shown in Table 1.
[0073] The above embodiments demonstrate that introducing Bi into the SBT matrix... 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 significantly affects the energy storage performance of ceramics, effectively improving the low energy density of SBT-based ceramic dielectric materials and increasing the breakdown field strength and recoverable energy density. The prepared SBT-based energy storage ceramic dielectric material achieved the optimal energy density of 5.37 J / cm³. 3 The energy storage efficiency is 84.4%, and the energy storage performance fluctuates very little over a wide temperature and frequency range, exhibiting excellent temperature and frequency stability. Furthermore, it can achieve high polarization under low electric fields. Therefore, this ceramic can meet the application scenarios of pulsed power energy storage and is suitable for a wide range of operating temperatures, frequencies, and application fields. In one embodiment, the present invention provides a strontium bismuth titanate-based dielectric ceramic material for electronic power, military, and high-energy pulsed power technologies as described in any of the above embodiments. The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. Table 1 Components Dielectric constant Dielectric loss Energy storage density Energy storage efficiency x=0.05 842.6659 0.00016 4.42 85.51 x=0.10 656.0724 0.00023 3.10 86.78 x=0.15 495.6696 0.00017 5.32 85.68 x=0.20 390.1239 0.00013 5.37 84.40
Claims
1. A strontium bismuth titanate-based dielectric energy storage ceramic material that combines high energy density, low loss, and wide temperature and frequency stability, characterized in that, Its chemical composition is (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3, 0.05≤x≤0.
20.
2. The strontium bismuth titanate-based dielectric energy storage ceramic according to claim 1, characterized in that, The x values are 0.05, 0.10, 0.15, and 0.20; the optimal energy storage density of this ceramic is 5.37 J / cm3, and the energy storage efficiency is 84.4%; the energy storage performance fluctuates very little under wide temperature and frequency ranges.
3. A method for preparing a strontium bismuth titanate-based dielectric energy storage ceramic material with high energy storage density, low loss, and wide temperature and frequency stability as described in any one of claims 1-2, characterized in that, Includes the following steps: (1) Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio of the strontium bismuth titanate-based dielectric energy storage ceramic material with high energy storage density, low loss and wide temperature and frequency stability as described in any one of claims 1-2, ball mill the mixture and calcine it to obtain (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 )O3 powder, 0.05≤x≤0.20; (2) The (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder was subjected to secondary ball milling, granulation, molding, and debinding to obtain (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 Strontium bismuth titanate-based dielectric energy storage ceramic blank; (3) The (1-x)Sr 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 The strontium bismuth titanate-based dielectric energy storage ceramic blank was sintered and silvered to obtain the strontium bismuth titanate-based dielectric energy storage ceramic material.
4. The preparation method according to claim 3, characterized in that, The synthesis method involves heating to 800-950°C in a muffle furnace at a rate of 5°C / min, holding at that temperature for 2-4 hours, and then cooling to room temperature with the furnace to obtain (1-x)Sr. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 powder is then milled twice and dried at a constant temperature of 80℃.
5. The preparation method according to claim 3, characterized in that, The granulation process involves mixing the dried powder obtained after the second grinding with a 5% PVA solution, granulating the mixture, and then passing the granulated powder through a 60-mesh 304 stainless steel sieve. The granulated powder is then pressed under 2-3 MPa into (1-x)Sr particles with a diameter of 8 mm and a thickness of 1-1.2 mm. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 Strontium bismuth titanate-based dielectric energy storage ceramic blank.
6. The preparation method according to claim 3, characterized in that, The process of removing the adhesive involves heating the material at 2℃ / min to 600℃~650℃ and holding it at that temperature for 3~4 hours, followed by cooling it in the furnace to obtain a ceramic blank.
7. The preparation method according to claim 3, characterized in that, The sintering process involves sintering the ceramic green body obtained after debinding at 1200~1250℃ and holding it at that temperature for 2 hours. The temperature is increased at a rate of 10℃ / min to 1000℃, followed by a rate of 5℃ / min. After the holding period, the green body is cooled in the furnace.
8. The preparation method according to claim 3, characterized in that, The silver coating process involves polishing the sintered and cooled sheet, ultrasonically cleaning it, brushing it with high-temperature silver paste, and then heating it to 600℃~700℃ at a rate of 5℃ / min and holding it at that temperature for 10 minutes.
9. A (1-x)Sr as described in claim 1 for use in fields such as electronic power, military, and high-energy pulsed power technology. 0.7 Bi 0.2 TiO3-xBi 2 / 3 (Mg 1 / 3 Nb 2 / 3 O3 Strontium bismuth titanate-based dielectric energy storage ceramic material, wherein x is 0.05, 0.10, 0.15 or 0.20.